Genome Editing in Rice: Recent Advances, Challenges, and Future Implications - Mishra, Rukmini; Joshi, Raj Kumar; Zhao, Kaijun (Frontiers in Plant Science, 2018)
Rice (Oryza sativa L.) is the major food source for more than 3 billion people of the world. In the last few decades, the classical, mutational and molecular breeding approaches have brought about tremendous increase in rice productivity with the development of novel rice varieties. However, stagnation in rice yield has been reported in recent decade owing to several factors including the emergence of pests and phyto pathogens, climate change and other environmental issues posing great threat to global food security. There is an urgent need to produce more rice and associated cereals to satisfy the mammoth task of feeding a still growing population expected to reach 9.7 billion by 2050. Advances in genomics and emergence of multiple genome-editing technologies through use of engineered site-specific nucleases (SSNs) have revolutionized the field of plant science and agriculture. Among them, the CRISPR/Cas9 system is the most advanced and widely accepted because of its simplicity, robustness and high efficiency. The availability of huge genomic resources together with a small genome size makes rice more suitable and feasible for genetic manipulation. As such, rice has been increasingly used to test the efficiency of different types of genome editing technologies to study the functions of various genes and demonstrate their potential in genetic improvement. Recently developed approaches including CRISPR/Cpf1 system and base editors have evolved as more efficient and accurate genome editing tools which might accelerate the pace of crop improvement. In the present review, we focus on the genome editing strategies for rice improvement, highlighting the applications and advancements of CRISPR/Cas9 system. This review also sheds light on the role of CRISPR/Cpf1 and base editors in the field of genome editing highlighting major challenges and future implications of these tools in rice improvement.